Amino-decorated bis(pyrazolate) metal–organic frameworks for carbon dioxide capture and green conversion into cyclic carbonates. Issue 2 (15th January 2019) - Vismara, Rebecca; Tuci, Giulia; Mosca, Nello; Domasevitch, Kostiantyn V.; Di Nicola, Corrado; Pettinari, Claudio; Giambastiani, Giuliano; Galli, Simona; Rossin, Andrea
Abstract : The amino-tagged bis(pyrazolate) MOFZn(BPZNH2 ) is an excellent CO2 adsorbent and CO2 epoxidation catalyst under green conditions. Abstract : The novel Metal–Organic Frameworks (MOFs)M(BPZNH2 ) (M = Zn, Ni, Cu) were prepared from the reaction of the corresponding metal acetates M(OAc)2 · n H2 O and the organic linker 3-amino-4, 4′-bipyrazole (H2 BPZNH2 ) under solvothermal conditions. H2 BPZNH2 was obtained straightforwardly from the reduction of the related nitro-compound using hydrazine as a reducing agent. The Zn(ii ) polymer is characterized by a 3D porous network featuring tetrahedral metallic nodes and bridging BPZNH2 2− anions defining the vertices and edges of square channels. The isostructural Ni(ii ) and Cu(ii ) MOFs show square-planar metallic nodes and bridging BPZNH2 2− spacers at the vertices and edges of the rhombic channels of a 3D porous framework. All the MOFs were characterized in the solid state [(VT)-PXRD, IR, TGA-DTG]. The textural property analysis revealed that they are micro–mesoporous materials with BET specific surface areas (SSAs) falling in the 100–400 m 2 g −1 range.Zn(BPZNH2 ), showing the highest SSA (395 m 2 g −1 ) and a prevalently microporous texture (micropore area = 69% of the accessible SSA), has been exploited as a CO2 capture material: at T = 298 K and p CO2 = 1 bar, the total gas uptake equals 3.07 mmol g −1 (13.5 wt% CO2 ). Its affinity for CO2 (isosteric heat of adsorption Q st = 35.6 kJ mol −1 ; CO2 /N2 Henry selectivity = 17; CO2 /N2 IAST selectivity = 14) is higher than that of its nitro-functionalized analogue and comparable to that of other amino-decorated MOFs from the literature. Finally, Zn(BPZNH2 ) was tested as a heterogeneous catalyst in the reaction of CO2 with activated epoxides bearing a –CH2 X pendant arm (X = Cl: epichlorohydrin; X = Br: epibromohydrin) to give the corresponding cyclic carbonates at T = 393 K and p CO2 = 1 bar under green (solvent- and co-catalyst-free) conditions. A good conversion of 47% and a TOF of 3.9 mmol(carbonate) (mmolZn ) −1 h −1 were recorded with epibromohydrin.